Dido mutations trigger perinatal death and generate brain abnormalities and behavioral alterations in surviving adult mice - Villares, Ricardo (Proc Natl Acad Sci U S A, 2015)
Nearly all vertebrate cells have a single cilium protruding from their surface. This threadlike organelle, once considered vestigial, is now seen as a pivotal element for detection of extracellular signals that trigger crucial morphogenetic pathways. We recently proposed a role for Dido3, the main product of the death inducer-obliterator (dido) gene, in histone deacetylase 6 delivery to the primary cilium [Sánchez de Diego A, et al. (2014) Nat Commun 5:3500]. Here we used mice that express truncated forms of Dido proteins to determine the link with cilium-associated disorders. We describe dido mutant mice with high incidence of perinatal lethality and distinct neurodevelopmental, morphogenetic, and metabolic alterations. The anatomical abnormalities were related to brain and orofacial development, consistent with the known roles of primary cilia in brain patterning, hydrocephalus incidence, and cleft palate. Mutant mice that reached adulthood showed reduced life expectancy, brain malformations including hippocampus hypoplasia and agenesis of corpus callosum, as well as neuromuscular and behavioral alterations. These mice can be considered a model for the study of ciliopathies and provide information for assessing diagnosis and therapy of genetic disorders linked to the deregulation of primary cilia.